2013
DOI: 10.5194/nhess-13-361-2013
|View full text |Cite
|
Sign up to set email alerts
|

Climate-induced landslide reactivation at the edge of the Most Basin (Czech Republic) – progress towards better landslide prediction

Abstract: Abstract. The catastrophic landslide at Eisenberg in North Bohemia was reactivated during January 2011. This study integrates a range of geoscientific evidence in order to constrain the spatial and temporal development of this reactivation. It has investigated long-term geodetic measurements to assess the morphological development of the site over the last two decades. There is evidence to suggest that, over this period, the site had been subjected to progressive deformation caused by the collapse of an old mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 14 publications
2
17
0
Order By: Relevance
“…According to Hurník (1982), the removal of millions of tons of overburden material per year (in the 1970s and 1980s) could have caused the elastic lifting of the mountain massif and the destabilization of the upper part of the slope. In this regard, recent studies (Burda et al, 2011;Burda et al, 2013) confirmed an influence of mining, mainly in the mountains' piedmont, where the basin sediments were exposed during excavations.…”
Section: Geological Settingmentioning
confidence: 90%
See 1 more Smart Citation
“…According to Hurník (1982), the removal of millions of tons of overburden material per year (in the 1970s and 1980s) could have caused the elastic lifting of the mountain massif and the destabilization of the upper part of the slope. In this regard, recent studies (Burda et al, 2011;Burda et al, 2013) confirmed an influence of mining, mainly in the mountains' piedmont, where the basin sediments were exposed during excavations.…”
Section: Geological Settingmentioning
confidence: 90%
“…A dramatic slope deformation which started in 1952 (Rybář, 1997) resulted in the abandonment of the village of Eisenberg, but mining operations continued in the form of open-cast exploitation (Burda et al, 2013). According to Hurník (1982), the removal of millions of tons of overburden material per year (in the 1970s and 1980s) could have caused the elastic lifting of the mountain massif and the destabilization of the upper part of the slope.…”
Section: Geological Settingmentioning
confidence: 99%
“…There is clear in di ca tion of a low-re sis tiv ity (20-100 Wm) zone con tin u ing along the scarp and fur ther into the bed rock. Sim i lar fea tures are typ i cal for cross ing a sub-verti cal tec tonic line, usu ally a fault (Burda et al, 2013;Hartvich and Valenta, 2013).…”
Section: Fig 7 Lon Gi Tu DI Nal and Trans Verse Pro Files Of The Ermentioning
confidence: 99%
“…The monitoring is implemented in areas where the occurrence of shifts and deformations is probable or has already been manifested. Landslides cause natural disasters or limit the territorial development in many countries worldwide being the subject of great research interest (Pesci et al 2004;Burda et al 2013).…”
Section: Introductionmentioning
confidence: 99%